PKM PENDAMPINGAN TEKNIS, MANAGERIAL DAN E-MARKETING PENGOLAH POKEA ASAP DALAM RANGKA PENINGKATAN PENDAPATAN PASCA COVID-19 - Sadimantara, Muhammad Syukri; Sakir, Sakir; Isamu, Kobajashi T; Suwarjoyowirayatno, Suwarjoyowirayatno; Nangi, Laode Jumadil (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2021)
AbstractPuuwangudu Village, Asera District, North Konawe Regency is one of the fisheries-based areas with one of the main commodities being Pokea. However, the potential of Pokea cannot be optimized by the local community, that is, it is sold in the form of raw pokea or pokea dishes so that it does not provide more economic value because the price is low, and the shelf life is low so it doesn't. In fact, with a touch of technology, especially vacuum packaging technology and attractive packaging designs, it can increase added value in terms of price and quality. In addition to this, the main factor in the lack of income is because pokea processed products cannot reach a wider market such as supermarkets and shops, this can be overcome by training in product licensing and business entities which are conditions for distributing products in supermarkets. In addition, in order to expand market share, online marketing training is needed on the website to increase their business income through e-marketing. The purpose of this PKM is the dissemination of technology and business management, especially smoked pokea processing through the stages of Participatory Technology Development, Community development, Persuasive and Educative . To keep maximizing PKM output and outcome were carried out such as the design and registration of IPR trademarks, packaging manufacture, assistance for product distribution permits and product socialization to local government stakeholders. The outcome of PKMI activities shows that all mothers who are members of the Partner Group are skilled at processing smoked pokea, can pack smoked pokea products with a vacuum sealer system, understand product labeling that meets standards and practice online marketing through website and social media.  The outcome of this service is expected to increase the income of smoked pokea processors, especially during the covid-19 pandemic.. Keywords: Smoked Pokea, Technical Assistance, Managerial Assistance, E-Commers. AbstrakDesa Puuwangudu, Kecamatan Asera, Kabupaten Konawe Utara merupakan salah satu wilayah yang berbasis perikanan dengan salah satu komoditas utamanya adalah Pokea. Namun potensi Pokea tersebut tidak mampu dioptimalkan oleh masyarakat setempat, yakni halnya di jual dalam bentuk pokea mentah atau masakan pokea sehingga tidak memberikan nilai ekonomis lebih karena harganya rendah, dan masa simpan yang rendah sehingga tidak. Padahal dengan sentuhan teknologi terutama teknologi pengemasan vaccum dan desain kemasan yang menarik maka dapat meingkatkan nilai tambah dari segi harga maupun mutu. Selain hal tersebut faktor utama kurangnya pendapatan adalah karena produk olahan pokea tidak dapat menjangkau pasar yang lebih luas seperti swalayan dan toko, hal ini dapat diatasi dengan pelatihan pengurusan perizinan produk dan badan usaha yang menjad syarat mengedarkan produk di swalayan. Selain itu dalam rangka memperluas pangsa pasar dibutuhkan pelatihan pemasaran online pada website untuk meningkatkan pendapatan usaha mereka melalui e marketing.. Tujuan dari PKM  ini adalah untuk  diseminasi teknologi dan manjemen pengelolaan usaha khusunya pengolahan pokea asap  melalui metode Persuasif dan  Edukatif. Untuk menjaga memaksimalkan output dan outcame PKM, dilakukan penyuluhan  seperti desain dan pendaftran HKI merek dagang, pembuatan kemasan, pendampingan ijin edar produk dan sosialisasi produk kepada stakholder pemerintah daerah. Outcame dari kegiatan PKMI   menunjukkan bahwa semua ibu-ibu yang tergabung dalam kelompok  mitra telah terampil mengolah pokea asap, dapat mengemas produk pokea asap dengan system vacuum sealer, memahami pelabelan produk yang memenuhi standard dan  mempraktekkan pemasaran online melalui situs dan media social.  Outcame dari pengabdian ini diharapkan dapat meningkatkan pendapatan pelaku pengolah pokea asap terutama dalam masa pandemic covid-19. Kata Kunci:  Pokea Asap, Pendampingan Teknis, Pendampingan manajerial, E- Commers.